In memoriam Jacques Tixier (1925–2018) - Mester, Zsolt (Dissertationes Archaeologicae, 2019)
On 3rd April 2018, the world-famous scholar Jacques Tixier died at the age of 93. He was the last one of the three great French prehistorians who made fundamental imprints on prehistoric archaeology after World War 2.